Human Capital Formation and Changes in Low Pay Persistence - Kabir Dasgupta; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
This study aims at understanding how persistence in low pay changes over time. In particular, we extend the existing literature on human capital formation by documenting heterogeneity in low pay persistence by age and human capital level. We utilise population-wide tax ecords to track monthly labour market trajectories of workers who are observed in low paid employment during the initial period of analysis. Performing age- and qualification-specific regressions, our empirical findings indicate that low pay persistence reduces with time. However, the magnitude is highly heterogeneous acorss the workforce. For a qualified worker in their early 20s, the risl of staying on low-pay declines by, on average, 5 to 10% points after one year - while for a worker in their 50s, independent of their qualification level, persistence remains almost unchanged. We find a strong association between decline in low-pay persistence and the firm's average wage level.
Keywords: J63; J61; J24; 330; low pay; human capital formation; state dependence; random-effects probit; intital condition; unobserved heterogeneity